Analisis Hasil Elektroforesis DNA dengan Image Processing Menggunakan Metode Gaussian Filter - Khairul Anam; Widya Cahyadi; Ihsanul Azmi; Kartika Senjarini; Rike Oktarianti (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2021)
DNA gel electrophoresis plays an important role in the development of science. However, the process of manually analyzing DNA size is still relatively difficult, time-consuming, and often results an error. This study proposed electrophoresis process using image processing with Gaussian Filter method. Gaussian Filter is used to improve the quality of the image which makes the image clearer. The method was applied using python programming and then embedded into Raspberry pi 3 module. This modul processed images taken by Raspberry pi V1 camera. To realize these taken images, tracking mouse was used. All the images which had been processed were displayed on LCD touchscreen 5 inch. The result shows that the study using Gaussian Filter indicates good performance. This is proved by the lowest error percentage of 0,20% . In addition, compared to previous studies, the largest error percentage is still relatively smaller at 12.41%.